Shout It Out Loud: K-Pop Fan Chants by Seventeen's Carat and Twice's Once - Candika Primatin Saputri; Yessika Indah Cahyani; Novita Maharani; Istiqomah; Maharatna Fahma Poetri Purnomo (Studies in Language, Education, and Culture (SeLEC), 2026)
This study examines the structure, function, and symbolism of K-pop fan chants within the fandoms of SEVENTEEN (Carat) and TWICE (Once). Using a descriptive qualitative approach, the study analyzes official fan chant guides, live performance recordings, and fan-made fancam videos uploaded to YouTube. The analysis focuses on how collective chanting functions as a performative expression of fandom identity and emotional participation. The findings reveal that fan chants serve not only as forms of vocal support but also as social rituals that foster solidarity, social recognition, and collective identity among fans. Once’s cheerful chants reflect warmth and inclusivity, while Carat’s synchronized and powerful chants symbolize loyalty and unity. In addition, concert moments documented through fancams are transformed into enduring digital memories that strengthen global fandom networks and sustain emotional connections among fans across geographical boundaries. This study demonstrates that fan chants represent a dynamic interaction between voice, emotion, and social identity, transforming concert spaces into participatory communities built upon shared experiences. The findings contribute to the understanding of contemporary digital popular culture by highlighting how fan practices function as complex social rituals that shape and maintain collective identity in both physical and virtual spaces. Furthermore, this study offers insights into the strategic role of fan engagement in building and sustaining loyal global communities.